A Hybrid Algorithm to Protect Computer Networks Based on Human Biometrics and Computer Attributes - Ogla, Rahim Abdul-Al Sahib (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Objective of this work is the mixing between human biometric characteristics and unique attributes of the computer in order to protect computer networks and resources environments through the development of authentication and authorization techniques. In human biometric side has been studying the best methods and algorithms used, and the conclusion is that the fingerprint is the best, but it has some flaws. Fingerprint algorithm has been improved so that their performance can be adapted to enhance the clarity of the edge of the gully structures of pictures fingerprint, taking into account the evaluation of the direction of the nearby edges and repeat. In the side of the computer features, computer and its components like human have unique characteristics. A program has been produced in the Visual Basic environment. The goal of this program is to get the computer characteristics and merge them with human characteristics to produce powerful algorithms of authentication and authorization can be used to protect the resources that are stored in the computer networks environments through the creation of software modules and interactive interfaces to accomplish this purpose.